Screening of Three Exons of PKD1 gene In Five Patients with Autosomal Polycystic Kidney Disease - Tabagh, Refaat M.; Shebani, Abdulhafid A.; Zaid, Ahmed; Marwan, Mohamed M. B. (The Libyan Journal of Science, 2022)
Autosomal dominant polycystic kidney disease (ADPKD) is one of the most common genetic kidney disorders with the incidence of 1 in 1,000 births. ADPKD is genetically heterogeneous with two genes identified: PKD1 (16p13.3, 46 exons) and PKD2 (4q21, 15 exons). Eighty five percent of the patients with ADPKD have at least one mutation in the PKD1 gene and fifteen percent of the patients have one mutation in PKD2 gene. Direct sequencing of one patient and his sequence of PKD1 gene demonstrated a missense mutation GCC----CCC substitution in exon 13 with cause change amino acid of Alanine to Proline at codon 1029. Three brothers have deletion mutation in exon 15, one patient missense mutation GGC---GCC in exon 19 which cause change amino acid of Glycine to Alanine at codon 2530. Molecular diagnostics of ADPKD relies on mutation screening of PKD1 and PKD2, which is complicated by extensive allelic heterogeneity and the presence of six highly homologous sequences of PKD1. PCR strategy was used to screen sequence variants with heteroduplex analysis and several affected individuals were discovered to have clusters of base pair substitutions in exons 13 and 19 with del 20 pb (3601-3620) in exon15.